2009
DOI: 10.1089/apc.2008.0190
|View full text |Cite
|
Sign up to set email alerts
|

AIDS Orphanages in China: Reality and Challenges

Abstract: With the increasing number of AIDS orphans in China, the government has been building AIDS orphanages since 2004 to accommodate some of those children who have lost both parents to AIDS. However, no data are available regarding the quality of this model of institutional care of AIDS orphans in China. This study, based on qualitative data from children and workers in AIDS orphanages, examines the daily lives, needs, and feelings of orphans and explores the advantages and disadvantages of institutionalized care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…These findings were consistent with results of one previous qualitative study among orphanage orphans in China, which suggested that most children in orphanages knew little about AIDS and the knowledge of AIDS was even more limited among younger children . One of the reasons perceived by children in the AIDS orphanage for the lack of AIDS knowledge was that their caregivers (orphanages workers) or school teachers purposely avoid discussing the topic of AIDS with them because of the fears of upsetting the children who lost both of their parents to HIV (Zhao, Li, Kaljee, et al, 2009). One of the possible explanations in the current study for the lower AIDS knowledge among HIV-affected children might also be that persons around them purposely avoid discussing AIDS and the children might also try to avoid conversation or discussion about AIDS because of their devastating memories associated with AIDS-related loss in their families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings were consistent with results of one previous qualitative study among orphanage orphans in China, which suggested that most children in orphanages knew little about AIDS and the knowledge of AIDS was even more limited among younger children . One of the reasons perceived by children in the AIDS orphanage for the lack of AIDS knowledge was that their caregivers (orphanages workers) or school teachers purposely avoid discussing the topic of AIDS with them because of the fears of upsetting the children who lost both of their parents to HIV (Zhao, Li, Kaljee, et al, 2009). One of the possible explanations in the current study for the lower AIDS knowledge among HIV-affected children might also be that persons around them purposely avoid discussing AIDS and the children might also try to avoid conversation or discussion about AIDS because of their devastating memories associated with AIDS-related loss in their families.…”
Section: Discussionmentioning
confidence: 99%
“…AIDS orphanages were set up to meet orphans' basic needs: food, living quarters, medical care, and education (Zhao, Li, Kaljee, et al, 2009). The orphanages were mainly funded by the local government or nongovernmental organizations.…”
mentioning
confidence: 99%
“…Briefly, the AIDS orphans living in centralized care settings were recruited from two government-funded orphanages in each of the two counties and the eight community-based group homes for children orphaned by AIDS in one county [27]. The AIDS orphans and vulnerable children from the family and extended family care settings were recruited with assistance of the village leaders who helped us to generate lists of families caring for orphans or families with confirmed diagnosis of parental HIV infection.…”
Section: Methodsmentioning
confidence: 99%
“…These consequences would further facilitate the transmission of HIV. In China, there is however, a lack of psychological support services and interventions targeting PLWH in general and HIVMSM in particular [1315]. The World Health Organization has also reported the shortage of psychological support services to MSM [16].…”
Section: Introductionmentioning
confidence: 99%